If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22(x + -3) = 132 Reorder the terms: 22(-3 + x) = 132 (-3 * 22 + x * 22) = 132 (-66 + 22x) = 132 Solving -66 + 22x = 132 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '66' to each side of the equation. -66 + 66 + 22x = 132 + 66 Combine like terms: -66 + 66 = 0 0 + 22x = 132 + 66 22x = 132 + 66 Combine like terms: 132 + 66 = 198 22x = 198 Divide each side by '22'. x = 9 Simplifying x = 9
| 5y+11=-4y-2y | | 20x-15=17x-7 | | 3*P/2 | | ax^2+bx+b-a=0 | | C-16=54 | | 6x-5=2(15-2x) | | 7n-1=6 | | 2(2x+3)=3(2x+2) | | 2x=(x-4)(x-4) | | -8+18m=46 | | -3x+8y=-16 | | 18sin(x)(cos(x)-1)=0 | | 1+8c=6c+21 | | 3p=9p | | -x+8x+32=0 | | 4p+10=90 | | 86-m=4 | | 12-2(a-1)=5 | | -4(2x-6)+5=-8x+29 | | 4w-15=17 | | 1998*9878= | | 5x+4x-3x-5=31 | | 5(j-2)=2j+6 | | 15-5XL=25 | | 2x*2+3x-90=0 | | rx=x | | 3x-26=24 | | 2+5(X+3)-3(X-4)=2(2X+4) | | 2x+13x=60 | | 8-4y=0 | | 54=24+5b | | x^2+4x+y^2-4y-8=0 |